2013
DOI: 10.3109/16066359.2013.806651
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol in the life narratives of women: Commonalities and differences by sexual orientation

Abstract: Aim The aim of this study was to explore social representations of alcohol use among women, with a focus on possible differences between sexual minority and heterosexual women. Methods This qualitative study was part of a larger study examining mediators of heavier drinking among sexual minority women (lesbian identified, bisexual identified, and heterosexual identified with same sex partners) compared to heterosexual women based on the National Alcohol Survey. Qualitative in-depth life history interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Studies comparing qualitative results from telephone vs. face-to-face interviews have documented no significant differences between methodologies (Sturges & Hanrahan, 2004). Interviews by telephone may have the added advantage of reducing biases (e.g., social desirability) associated with divulging sensitive information due to increased feelings of anonymity, and they can capture hard-to-reach and diverse populations, regardless of geographical location (Drabble & Trocki, 2014; Drabble et al, 2010; Novick, 2008; Opdenakker, 2006; Waterman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing qualitative results from telephone vs. face-to-face interviews have documented no significant differences between methodologies (Sturges & Hanrahan, 2004). Interviews by telephone may have the added advantage of reducing biases (e.g., social desirability) associated with divulging sensitive information due to increased feelings of anonymity, and they can capture hard-to-reach and diverse populations, regardless of geographical location (Drabble & Trocki, 2014; Drabble et al, 2010; Novick, 2008; Opdenakker, 2006; Waterman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted with sexual minority and heterosexual cisgender women found that the meaning of alcohol consumption in fostering community connection was more salient for sexual minority cisgender women and similar meanings may help understand alcohol and drug use in sexual minority transwomen (Drabble & Trocki, 2014). Are there specific environments and conditions – physical, discursive, or ideological – embedded within hegemonic heteronormativity that protects heterosexual transwomen from the sexual minority health disparities identified in this study?…”
Section: Discussionmentioning
confidence: 99%
“…This also could be a product of socializing with other SMW in heavier drinking contexts. Despite changes in societal acceptance toward SMW, much of the socializing among the lesbian, gay, and bisexual community still occurs in heavier drinking settings (Drabble & Trocki, 2014; McKirnan & Peterson, 1989; Trocki et al, 2005), which may in turn lead to higher community perceived norms. This is the first study to evaluate differences between sexual minority specific and typical woman perceived normative drinking.…”
Section: Discussionmentioning
confidence: 99%